Ketajaman Penglihatan Berdasarkan Intensitas Bermain Game Pada Anak SD Kelas 5 dan 6 di SD Al-Rasyid Pekanbaru - Wiwik Norlita; Isnaniar; Tengku Wirdatul Hasanah (Sistem Informasi, 2020)
Eye is a sense of sight that humans have, through the human eye absorbs visual information used to carry out various activities. However, many problems with vision occur, ranging from mild disorders to severe disorders that can cause blindness. This sharp visual impairment is a problem in the community that will be encountered as long as there are no preventive measures from early on. Research Objectives To find out the visual acuity based on the intensity of playing games in 5th and 6th grade children of Al-Rasyid Elementary School Pekanbaru. This type of research is descriptive with the number of 75 class 5 and 6 respondents in Pekanbaru Al-Rasyid Elementary School. Data collection techniques in this study used a questionnaire and by measuring the sharpness of the eyes of respondents using snellen charts, visual sharpness was said to be normal ≥ 6/6. Sampling by simple random sampling means that sample taken researchers from grade 5 and 6 students at random who are willing to participate in research at Al-Rashid SD Pekanbaru on 14 to 18 February 2019. The results of study the general of the results of this study found that The number of 75 respondents regarding the description of visual acuity based on the intensity of playing games in grade 5 and 6 children at Al-Rasyid Elementary School Pekanbaru, obtained by children with normal vision as many as 52 respondents (69.3%) and children with abnormal vision as many as 23 respondents (30, 7%). Expected to parents is keep your eyes healthy children by reducing the time to play the game or give the child to play the gadget at certain times, in addition to the parents should be able to explain to their children about eye health and the impact of theplay, gamethen parents should increase knowledge about health and the impact of playing games.